Early Templar Administration in Provence and North-Eastern Spain - Alan Forey (Medievalista)
Information about the creation of Templar convents and a province in Provence, north-eastern Spain and neighbouring territories before 1150 is limited. Some types of evidence, however, suggest the establishment of convents. These include references to the construction of buildings to house Templars; the introduction of the term magister to describe some local officials; lists of brothers resident in a particular place; the appearance of the offices of claviger (“keeper of the keys”) and chaplain; and the close links formed between some laymen and Templar communities. It is clear that some convents were also setting up dependencies or granges by the middle of the 12th century. From very early on, there was a Templar official with authority on both sides of the Pyrenees, and he came to be given the title of magister, although the first reference to the province of “Provence and a certain part of Spain” does not occur until 1143. It is possible, though not certain, that provincial chapters began to be convened before 1150.